Effect of Ketogenic Diets on Cardio-Metabolic Outcomes in Cancer Patients: A Systematic Review and Meta-Analysis of Controlled Clinical Trials. (13th December 2022) - Amanollahi, Alireza; Khazdouz, Maryam; Malekahmadi, Mahsa; Klement, Rainer J.; Lee, Derek; Khodabakhshi, Adeleh
Abstract: In this systematic review and meta-analysis of clinical controlled trials (CCTs) we aimed to investigate the efficacy of KDs as an adjuvant therapy on cardiometabolic outcomes in patient with cancer compared to conventional non-ketogenic diets. Only CCTs involving cancer patients that were assigned to either a KD or a standard diet control group were selected. Two reviewers independently extracted the data, and a meta-analysis was performed using a random effects model to estimate weighted mean differences (WMDs) and confidence intervals (CIs) in body composition, metabolite, lipid profile, liver and kidney function parameters and quality of life. This meta-analysis showed a significant reduction in body weight (WMD= −2.99 kg; 95% CI: −4.67, −1.31; and P  < 0.001), BMI (WMD= −1.08 kg/m 2 ; 95% CI: −1.81, −0.34; P  ≤ 0.002) and fat mass (WMD= −1.48 kg; 95% CI: −2.56, −0.40; and P  = 0.007) by a KD. KDs significantly decreased glucose (WMD= −5.22 mg/dl; 95% CI: −9.0, −1.44; and P  = 0.007), IGF-1 (WMD= −17.52 ng/ml; 95% CI: −20.24, −14.8; and P ˂0.001) and triglyceride (WMD= −24.46 mg/dl; 95% CI: −43.96, −4.95; and P  = 0.014) levels. Furthermore, KDs induced ketosis by increasing β-hydroxybutyrate (WMD= 0.56 mmol/l; 95% CI: 0.37, 0.75; and P  < 0.001). There were non-significant pooled effects of KDs on improving insulin, C-reactive protein and cholesterol levels and kidney and liver function. Emotional functioning was even increased significantly in the KD compared to the SD groups. In summary we found that KDs result in a greater reduction in glucose, IGF-1, triglycerides, body weight, BMI, and fat mass in cancer patients compared to traditional non-ketogenic diets and improved emotional functioning. The quality of evidence in the meta-analysis was moderate according to the Nutrigrade assessment.